Mitochondrial microsatellite genomic instability and brafv600e mutation in central nervous system tumors - Radzak, Siti Muslihah Abd (2020)
The central nervous system tumor is known as one of the fatal cancers worldwide. The accumulation of multiple genetic alterations of the nuclear and mitochondrial genome is believed to be engaged in brain tumorigenesis. Mitochondrial microsatellite instability (mtMSI) is a change in repetitive sequences of the mitochondrial genome, has been described as a high occurrence in several human cancers. Meanwhile, the BRAFV600E is the most prevalent mutated nuclear oncogene that has been identified in multiple malignancies. Nevertheless, mtMSI and BRAFV600E mutation in brain tumor cases have not been reported in Malaysia, so far. Therefore, this study aims to determine the mtMSI status and BRAFV600E mutation in a series of Malay patients with brain tumors and to evaluate their association with clinicopathological features. The mtMSI alterations and BRAFV600E mutations were examined in a total of 50 paired brain tumor tissues and blood samples. The mtMSI status was analysed using mtMSI specific primers and the results were compared with the revised Cambridge References Sequences (rCRS). For the analysis of the BRAFV600E mutation, the PCR-RLFP assay was used for sequence variation, followed by direct sequencing and aligned using BLAST from the NCBI site. The results revealed eight mtMSI alterations were detected in D310 and D16184 of the displacement loop (D-loop) region (16%). Of these, one alteration C5TC4>C8TC in the D16184 region has not been previously reported in the MITOMAP database identified in this study. No association was found between mtMSI status and clinicopathological data. Additionally, BRAFV600E mutation has been detected in 11 out of 50 patients (22%). Similarly, no significant association between clinical features with BRAFV600E mutation observed in this study. The correlation between mtMSI status and BRAFV600E mutation also was analysed, however, no association identified between both alterations in all screened patients. This study provides insights into mitochondrial genome instability and BRAF mutation of brain tumor patients. A more detailed analysis involving a large number of patients is needed to establish the exact role of these genetic alterations in brain tumor cases in the Malay population.